Surgery in a Patient with Haemophilia A and Lymphoma - M. S. Cruz; J. Santillan; J. Lesser; J. Ortiz; L. Forzani; P. Plaza (Case Reports in Hematology)
An increased incidence of haematologic malignancies and other cancer types among patients with haemophilia compared with matched controls has been reported in several longitudinal studies. Tumours initially misdiagnosed as haematomas and conversely haematomas mistaken for tumours have been reported. Here, we describe the case of a 43-year-old man with severe haemophilia A and a diffuse large B-cell lymphoma, originally diagnosed as a haematoma, who underwent a splenectomy and several associated surgeries as part of his lymphoma treatment. Perioperative treatment with octanate® (human coagulation factor VIII) enabled the successful performance of all surgical interventions required in the context of lymphoma treatment. Nevertheless, differential diagnosis of posttraumatic haematoma in patients with haemophilia should include the consideration of malignancy.